ROWHOUSE RESIDENTS' ADAPTATION PATTERNS IN THE NEW NORMAL ERA (International Conference on Social and Islamic Studies, 2021)
The COVID-19 pandemic has forced people to work from home. Behavioral adjustments during the Covid-19 pandemic due to changes in work and study patterns from home have significantly impacted daily activities at home. However, the problem is that not all houses have a special space for work/study, especially for small-type dwellings with limited space. This study aims to reveal the form of adaptation in providing space to work from home and the level of comfort, especially for residents of row houses. The researcher uses a quantitative descriptive method in percentage figures to show the condition of community adaptation to the space to work and comfort level. This research was conducted by distributing questionnaires to 250 residents of row houses in Makassar. The results show that community adaptation in providing space to work from home is by function and modifying space. In space function, people generally use the living room as a workspace. The adaptation pattern is usually made by adding furniture, changing furniture, rearranging furniture. Meanwhile, to get comfort, respondents are generally influenced by two aspects. Aspects of the physical environment are significantly indicated by personal space and privacy. While aspects of the psychic environment were significantly shown in noise, spatial area, and air temperature. Although the space is limited and many distractions occur, most people claim they are pretty comfortable and feel more productive while working from home.